A survey on position-based routing in mobile ad hoc networks. - Mauve, M.
We present an overview of ad hoc routing protocols that make forwarding decisions based on the geographical position of a packet's destination. Other than the destination's position, each node need know only its own position and the position of its one-hop neighbors in order to forward packets. Since it is not necessary to maintain explicit routes, position-based routing does scale well even if the network is highly dynamic. This is a major advantage in a mobile ad hoc network where the topology may change frequently. The main prerequisite for position-based routing is that a sender can obtain the current position of the destination. Therefore, previously proposed location services are discussed in addition to position-based packet forwarding strategies. We provide a qualitative comparison of the approaches in both areas and investigate opportunities for future research
Keywords: Ad hoc routing protocols; Distance routing effect algorithm; Location services; Mobile ad hoc networks; Network node; Network topology; Packet destination geographical location; Position-based packet forwarding; Position-based routing